Diagnosis of electrocution: The application of scanning electron microscope and energy-dispersive X-ray spectroscopy in five cases. (March 2018) - Visonà, S.D.; Chen, Y.; Bernardi, P.; Andrello, L.; Osculati, A.
Highlights: Deaths from electricity do not have specific findings at the autopsy. Using common methods, the current mark cannot be differentiated from other kinds of thermal injuries. In electrocution, the detection and the identification of the metals embedded in the skin is essential. For this purpose, the microanalysis (scanning electron microscopy equipped with EDS probe) is an essential tool. The results of histology, ultrastructural morphology and microanalysis must be interpreted collectively. Abstract: Introduction: Deaths from electricity, generally, do not have specific findings at the autopsy. The diagnosis is commonly based on the circumstances of the death and the morphologic findings, above all the current mark. Yet, the skin injury due to an electrocution and other kinds of thermal injuries often cannot be differentiated with certainty. Therefore, there is a great interest in finding specific markers of electrocution. The search for the metallization of the skin through Scanning Electron Microscope equipped with Energy Dispersive X-Ray Spectroscopy (EDS) probe is of special importance in order to achieve a definite diagnosis in case of suspected electrocution. Materials and methods: We selected five cases in which the electrocution was extremely likely considering the circumstances of the death. In each case a forensic autopsy was performed. Then, the skin specimens were stained with Hematoxylin Eosin and Perls. On the other hand, the skin lesions were examined with a scanning electron microscope equipped with EDS probe in order to evaluate the morphological ultrastructural features and the presence of deposits on the surface of the skin. Results: The typical skin injury of the electrocution (current mark) were macroscopically detected in all of the cases. The microscopic examination of the skin lesions revealed the typical spherical vacuoles in the horny layer and, in the epidermis, the elongation of the cell nuclei as well as necrosis. Perls staining was negative in 4 out 6 cases. Ultrastructural morphology revealed the evident vacuolization of the horny layer, elongation of epidermic cells, coagulation of the elastic fibers. EDS-microanalysis: In the specimens collected from the site of contact with the conductor of case 1 and 2, the presence of the Kα peaks of iron was detected. In the corresponding specimens taken from cases 2, 4, 5 the microanalysis showed the Kα peaks of titanium. In case 3, titanium and carbon were found. Conclusions: In the suspicion of electrocution, the integrated use of different tools is recommended, including macroscopic observation, H&E staining, iron-specific staining, scanning electron microscopy and EDS microanalysis. Only the careful interpretation of the results provided by all these methods can allow the pathologist to correctly identify the cause of the death. Particularly, the present study suggests that the microanalysis (SEM-EDS) represents a very useful tool for the diagnosis of electrocution, allowing the detection and the identification of the metals embedded in the skin and their evaluation in the context of the ultrastructural morphology.